1990
DOI: 10.1073/pnas.87.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Induction of transcription from the long terminal repeat of Moloney murine sarcoma provirus by UV-irradiation, x-irradiation, and phorbol ester.

Abstract: The long terminal repeat (LTR) of Moloney murme sarcoma virus (Mo-MuSV) was used as a model system to study the stress response of mammalian cells to physical carcinogens. The chloramphenicol acetyltransferase (CAT) gene was inserted between two Mo-MuSV LTRs, and the LTR-CAT-LTR construct was used for virus production and was integrated into the genome of NIH 3T3 cells in the proviral form. This construct was used to assure that the integrated CAT gene was driven by the promoter of the LTR. Expression of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Exposure to ionizing radiation stimulated expression twofold, while treatment with H7, a nonspecific isoquinolinosulfonamide inhibitor of protein kinases, totally abrogated the response to x rays (34). Furthermore, preincubation with TPA to downregulate protein kinase C also abolished the response of x rays (34).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Exposure to ionizing radiation stimulated expression twofold, while treatment with H7, a nonspecific isoquinolinosulfonamide inhibitor of protein kinases, totally abrogated the response to x rays (34). Furthermore, preincubation with TPA to downregulate protein kinase C also abolished the response of x rays (34).…”
Section: Resultsmentioning
confidence: 98%
“…Although little is known about the intracellular signal transduction pathways activated by ionizing radiation, recent findings suggest the involvement ofprotein kinase C. In this regard, transcriptional activation of a construct containing the long terminal repeat ofMoloney murine sarcoma virus linked to the chloramphenicol acetyltransferase gene was examined after x irradiation (34). Exposure to ionizing radiation stimulated expression twofold, while treatment with H7, a nonspecific isoquinolinosulfonamide inhibitor of protein kinases, totally abrogated the response to x rays (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, transcriptional activation ofa construct containing the long terminal repeat of Moloney murine sarcoma virus linked to the chloramphenicol acetyltransferase gene was examined after gamma irradiation (39). Irradiation stimulated expression of the construct twofold, while treatment with H7, a nonspecific isoquinolinesulfonamide inhibitor of protein kinases, or preincubation with 12-O-tetradecanoylphorbol-1 3-acetate (TPA) to downregulate protein ki-nase C, abolished the response ofx rays (39). Similar inhibitory effects have been obtained with H7 and prolonged TPA stimulation during induction of TNF gene expression by ionizing radiation (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Like a number of eucaryotic promoters such as c-fos, metallothionein, and collagenase, known to be susceptible to DNA damaging agents and phorbol esters (7), retroviral promoters might be activated during the cascade of events triggered by the stress response. It has been recently reported that such activations by UV, x ray, and phorbol myristate acetate could occur in vitro for the Moloney murine sarcoma virus LTR (12). This effect is mediated by activation of the protein kinase C and would be independent of newly synthesized proteins.…”
Section: Discussionmentioning
confidence: 99%